2021
DOI: 10.3390/jcm10235489
|View full text |Cite
|
Sign up to set email alerts
|

Increased Geriatric Treatment Frequency Improves Mobility and Secondary Fracture Prevention in Older Adult Hip Fracture Patients—An Observational Cohort Study of 23,828 Patients from the Registry for Geriatric Trauma (ATR-DGU)

Abstract: Interdisciplinary orthogeriatric care of older adult hip fracture patients is of growing importance due to an ageing population, yet there is ongoing disagreement about the most effective model of care. This study aimed to compare different forms of orthogeriatric treatment, with focus on their impact on postoperative mobilization, mobility and secondary fracture prevention. In this observational cohort study, patients aged 70 years and older with a proximal femur fracture requiring surgery, were included from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Thus, modern concepts concerning the application of multidisciplinary care teams and specific care programs (e.g., increasing the number of visits by geriatricians, early geriatric rehabilitation program (EGR)) are keys to improving the surgical outcomes and patients’ quality of life. Previous studies had reported the outcomes of implementing these programs, which results in a significant increase in walking ability, early initiation of anti-osteoporotic agents for preventing secondary hip fractures, and decreased patient mortality [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, modern concepts concerning the application of multidisciplinary care teams and specific care programs (e.g., increasing the number of visits by geriatricians, early geriatric rehabilitation program (EGR)) are keys to improving the surgical outcomes and patients’ quality of life. Previous studies had reported the outcomes of implementing these programs, which results in a significant increase in walking ability, early initiation of anti-osteoporotic agents for preventing secondary hip fractures, and decreased patient mortality [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pathways along specific care programmes which facilitate e.g., increased geriatrician input, may enhance the likelihood of weight bearing by mitigating modifiable risk factors such as delirium which may be more prevalent among those with non-modifiable risk factors (e.g., those who are older and present with poor cognitive and functional status) [110]. Previous studies revealed that adopting these programmes leads to a considerable gain in walking capacity [111].…”
Section: Future Researchmentioning
confidence: 99%